PELAKSANAAN AANMANING PADA PERKARA WANPRESTASI PADA PUTUSAN VERSTEK LEMBAGA ARBITRASE DI INDONESIA - Made Cinthya Puspita Shara (Jurnal Restorative Justice, 2022)
Arbitration as an alternative dispute resolution effort must be determined by the parties based on an agreement to use the Arbitration Institution in civil cases in the future. As for this research, it shall discuss the implementation of the decision through a warning (aanmaning) based on the Arbitration Award which was decided by Verstek. The formulation of the problem in this research is how the process and legal product for the settlement of civil disputes and how the regulation of the implementation of security in default cases with Verstek Decisions based on the Indonesian Arbitration Institute. In this study using normative legal research methods using a substantial view. The results in this study are that the Arbitration Award is final and binding, which means it will immediately become the first and last level decision. The presence or absence of one of the parties in the arbitral tribunal does not stop the trial, making it possible for the arbitral tribunal to decide the case Verstek. The next effort is the process of warning (aanmaning) three times, if the opponent does not carry out the decision voluntarily. It is important to continue to apply this even in Arbitration cases, as an effort to pay off the obligations of the losing party in the trial.